Analysis of The Use of 12 Kg LPG (Liquified Petroleum Gas) Conveyance to Complaints of Household Workers - I Nyoman Sutarna; I Nengah Ludra Antara; Kadek Agus Mahabojana DP (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Manual conveyance is the work of transporting material carried out by workers to move material from an origin location to a destination location. The purpose of the study was to overcome the complaints experienced by housewives in the process of transporting 12kg LPG. The research was conducted using a two-period cross over design method. Musculoskeletal complaints experienced by housewives on the back, waist, knees and calves. Musculoskeletal complaints were measured using a Nordic Body Map questionnaire with a Likert scale, the data obtained were tested with independent t-test and t-pair. The results of the analysis showed that the use of 12 kg LPG conveyance could reduce musculoskeletal complaints from an average of 80.1 to 70 or decreased by 12.6%. It was concluded that the use of 12 kg LPG conveyance could reduce musculoskeletal complaints in housewives. It is recommended for those over 30 years of age to lift and carry heavy loads to use assistive devices.